2016
DOI: 10.1016/j.brainres.2016.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial regional hypothermia provides robust neuroprotection in a rat model of permanent middle cerebral artery occlusion with transient collateral hypoperfusion

Abstract: (248 words)The robust neuroprotective effects of transarterial regional hypothermia have been demonstrated in the typical transient middle cerebral artery occlusion (tMCAO) model, but have not yet been tested in other ischemic stroke models, even though clinical ischemic conditions are diverse. In order to clarify these effects in a different ischemic stroke model, we employed a rat model of permanent MCAO (pMCAO) with transient collateral hypoperfusion (tCHP), which was achieved by direct MCA ligation throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
(60 reference statements)
0
14
0
1
Order By: Relevance
“…SBH is more suitable for neuroprotection after stroke because it can quickly reach the target temperature and avoid the adverse effects associated with general hypothermia [37,38]. Moreover, transarterial regional hypothermia, which can achieve SBH, may exert strong neuroprotective effects in the MCAO with transient collateral hypoperfusion model [19]. In the present study, we prepared a hypothermia model following MCAO by perfusing cold saline through the ICA, and the results of cortical and rectal temperatures showed that SBH models were successfully established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SBH is more suitable for neuroprotection after stroke because it can quickly reach the target temperature and avoid the adverse effects associated with general hypothermia [37,38]. Moreover, transarterial regional hypothermia, which can achieve SBH, may exert strong neuroprotective effects in the MCAO with transient collateral hypoperfusion model [19]. In the present study, we prepared a hypothermia model following MCAO by perfusing cold saline through the ICA, and the results of cortical and rectal temperatures showed that SBH models were successfully established.…”
Section: Discussionmentioning
confidence: 99%
“…According to previously used successful parameters [19], 4 °C cold saline was infused (20 ml/kg) through the microcatheter placed in the right ICA via the external carotid artery for 15 min immediately after removal of the filament in the HT group. To eliminate the interference from hemodilution by saline infusion, we performed 37 °C warm saline infusion in the same manner in the NT group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A focal cerebral infarct was induced by permanent occlusion of the left distal middle cerebral artery (dMCAO) as previously described. [21,22] Briefly, a small craniotomy was made above the proximal segment of the middle cerebral artery (MCA), and the MCA was exposed after the dura was opened and retracted. The MCA was occluded by coagulation at the MCA segment just proximal to the olfactory branch.…”
Section: Stroke Model and Hypothermia Treatmentmentioning
confidence: 99%
“…As the MCA border is assumed to be the farthest margin occupied by an infarction due to MCAO, the MCA border may be considered the area where the ischemic region may be spared with a suitable neuroprotective treatment; the MCA border was anatomically defined as constant regions at 1.8 and 3.6 mm lateral from the midline, within the cortex corresponding to the edge of the brain supplied by the MCA. [21,29] The "ischemic core" was defined as the center of the ischemic lesion, well within the boundaries of the infarct. The "ischemic borderzone" was defined as the region immediately adjacent to the ischemic lesion, [15] as visually delineated by NeuN and DAPI staining.…”
Section: Immunohistochemistry and Image Analysismentioning
confidence: 99%